Effectiveness of junior faculty mentoring relationship in the College of Pharmacy - Gutierrez, Margarita M.; Sana, Erlyn A. (Manila The National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2015)
Faculty mentoring is associated with positive professional and personal outcomes, but here are no existing researches yet studying its occurrence in colleges of pharmacy in the Philippines. This research explores mentoring relationships and their effects. Specifically, the research aims to characterize junior faculty and mentors, described the mentoring profile, correlate the mentoring profile with mentoring effectiveness and career related outcomes, and correlated mentoring effectiveness with career related outcomes. The study is a cross sectional descriptive research with key informants interviews and survey as data collection procedures. Accessible populations are all colleges of pharmacy in the national capital region and no sampling was done. There were 13 deans, 80 junior faculty members and 34 identified mentors that participated in the study at 89% total response rate across the three groups of respondents. Results of the study shows that majority of mentoring relationships are between a junior faculty members and a relatively more senior faculty member. The faculty members are aware of the nature of the relationship although generally occurring in an informal and unstructured way. The benefits of mentoring relationships are appreciated and recognized by mentors and mentees as well as the dean and college officials. Benefits such as higher percentage of research involvement, higher frequency of administrative positions, and more career related outcomes are reported. However, most mentoring relationships are at the initiation phase, a factor that showed strong negative correlation with mentoring effectiveness score. On the other hand, having an institution-based and structured mentoring program showed a positive correlation for mentoring effectiveness score and has administrative advantages. The regression equation created from the analysis is [mentoring effectiveness score = 6.16+0.45 (cultivation phase) + 0.48 (formal mentoring program)]. Mentoring effectiveness score in turn has a positive impact on number of career related outcomes at a regression equation of [career related outcomes = 0.31 (mentoring effectiveness) ? 0.08]. Recommendations include the creation of institutionalized formal mentoring programs that includes the following characteristics. 1) Match junior faculty and mentor according to interest, expertise, and experience related to subject and research interest; 2) Mentor candidates who display willingness to commit time for face-to-face consultations. It is also more advantageous if the candidate mentor has a past mentoring history; 3). Design programs that are sustainable and long-term in order to maximize the benefits of the relationships that are observed at the cultivation stage; 4) Mentoring effectiveness score may be used as a tool to evaluate the strength of the relationship and the success of the program.
Thesis (Master of Health Professions Education)--University of the Philippines Manila, May 2015
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Jesus N. Sarol Jr. PhD, Reader/Critic; Imelda G. Peña PhD, Member; Monet M. Loquias PhD, Member; Roderick L. Salenga MPH, Member.
Keywords: Mentoring